Review paperThe use of reflectance confocal microscopy for examination of benign and malignant skin tumors - Wielowieyska-Szybińska, Dorota; Białek-Galas, Kamila; Podolec, Katarzyna; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Reflectance confocal microscopy (RCM) is a modern, non-invasive diagnostic method that enables real-time imaging of epidermis and upper layers of the dermis with a nearly histological precision and high contrast. The application of this technology in skin imaging in the last few years has resulted in the progress of dermatological diagnosis, providing virtual access to the living skin erasing the need for conventional histopathology. The RCM has a potential of wide application in the dermatological diagnostic process with a particular reference to benign and malignant skin tumors. This article provides a summary of the latest reports and previous achievements in the field of RCM application in the diagnostic process of skin neoplasms. A range of dermatological indications and general characteristics of confocal images in various types of tumors are presented.